2007
DOI: 10.1111/j.1462-2920.2007.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of Defluviicoccus‐related tetrad‐forming organisms in an anaerobic–aerobic activated sludge process

Abstract: A group of uncultured tetrad-forming organisms (TFOs) was enriched in an acetate-fed anaerobic-aerobic sequencing membrane bioreactor showing deteriorated enhanced biological phosphorus removal capacity. Based on 16S rRNA gene clone library and fluorescence in situ hybridization (FISH) analyses, these TFOs were identified as novel members of the Defluviicoccus cluster in the Alphaproteobacteria, accounting for 90 +/- 5% of the EUBmix FISH-detectable bacterial cell area in the reactor biomass. Microautoradiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 47 publications
4
52
0
Order By: Relevance
“…This analysis revealed that essentially all the observed Competibacteraceae cells assimilated glucose under both aerobic and anaerobic conditions (Supplementary Figure S3), thus supporting the ability for glucose assimilation and fermentation that is suggested by annotation of the C. denitrificans genome. The ability to ferment glucose and store PHA is shared with the Tetrasphaera japonica PAO and the Defluviicoccus vanus GAO (Wong and Liu, 2007). Interestingly, anaerobic energy demand for C. denitrificans may be supplemented by the excretion of lactate, produced from glycogen fermentation, in symport with a cation contributing to a PMF (Konings et al, 1984).…”
Section: Anaerobic Glycogen Metabolismmentioning
confidence: 99%
“…This analysis revealed that essentially all the observed Competibacteraceae cells assimilated glucose under both aerobic and anaerobic conditions (Supplementary Figure S3), thus supporting the ability for glucose assimilation and fermentation that is suggested by annotation of the C. denitrificans genome. The ability to ferment glucose and store PHA is shared with the Tetrasphaera japonica PAO and the Defluviicoccus vanus GAO (Wong and Liu, 2007). Interestingly, anaerobic energy demand for C. denitrificans may be supplemented by the excretion of lactate, produced from glycogen fermentation, in symport with a cation contributing to a PMF (Konings et al, 1984).…”
Section: Anaerobic Glycogen Metabolismmentioning
confidence: 99%
“…This is due in part to difficulties in acquiring their 16S rRNA sequence information in clone libraries generated from EBPR communities even where they are abundant (Meyer et al, 2006). Success has been achieved with prior enrichment (Wong et al, 2004;Meyer et al, 2006;Wong and Liu, 2007;McIlroy et al, submitted). Wong et al (2004) first proposed that putative alphaproteobacterial GAO may be related to Defluviicoccus vanus from clone sequences in a library constructed with alpha-proteobacterial targeted PCR primers.…”
mentioning
confidence: 91%
“…The probes Meyer et al (2006) published (DEF988 and DEF1020) were also designed so that together they targeted the whole cluster. A third Defluviicoccus 'cluster' (Wong and Liu, 2007) is based on a single 16S rRNA sequence only from a non-EBPR system but no FISH probes are available to detect it. Additional sequence data increasing the diversity among members of both clusters I and II have been reported (Wong and Liu, 2007), but the FISH probe designed to cover these for cluster II members (TFO_DF629) does not appear to work (Wong and Liu, 2007;McIlroy et al, submitted).…”
mentioning
confidence: 99%
See 2 more Smart Citations